2017
DOI: 10.1111/jog.13410
|View full text |Cite
|
Sign up to set email alerts
|

Moderate mammalian target of rapamycin inhibition induces autophagy in HTR8/SVneo cells via O‐linked β‐N‐acetylglucosamine signaling

Abstract: mTOR signaling inhibition played dual roles in regulating autophagy and apoptosis in HTR8/SVneo cells. Moderate mTOR suppression might induce autophagy via modulating O-GlcNAcylation of Beclin1 and SNAP29. Moreover, the negative interplay between Beclin1 O-GlcNAcylation and phosphorylation (Ser15) may be involved in autophagy regulation by mTOR signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The HBP and mTOR pathway share sensitivities for specific macromolecules and similar responses to fluctuations in nutrition, ( 12 14 , 16 , 17 , 23 25 , 32 , 36 , 37 ), leaving a wide door for exploring possible interactions. Recent evidence has suggested that mTOR and O-GlcNAc coordinate together to direct autophagy ( 54 , 55 ). Autophagy is the process of degrading and recycling organelles, as well as other cellular components, which is significant in maintaining cellular function ( 54 ).…”
Section: Sustained O-glcnacylation Correlates With Increased Phosphormentioning
confidence: 99%
See 2 more Smart Citations
“…The HBP and mTOR pathway share sensitivities for specific macromolecules and similar responses to fluctuations in nutrition, ( 12 14 , 16 , 17 , 23 25 , 32 , 36 , 37 ), leaving a wide door for exploring possible interactions. Recent evidence has suggested that mTOR and O-GlcNAc coordinate together to direct autophagy ( 54 , 55 ). Autophagy is the process of degrading and recycling organelles, as well as other cellular components, which is significant in maintaining cellular function ( 54 ).…”
Section: Sustained O-glcnacylation Correlates With Increased Phosphormentioning
confidence: 99%
“…Treatment with mTOR inhibitors Torin1 and PP242 resulted in induced autophagy and a drop in global O-GlcNAcylation, which occurred with increased OGA and decreased OGT protein expression ( 54 ). While it appears that mTOR inhibition couples with active autophagy, another study ( 55 ) demonstrated that the acuity of mTOR suppression impacts this dynamic; moderate mTOR suppression resulted in a significant increase in autophagy, but was attenuated with severe mTOR inhibition. What's more, an inter-play between phosphorylation and O-GlcNAcylation of the autophagy regulator, Beclin1, demonstrated that moderate mTOR suppression promoted the former modification, while severe inhibition increased the latter ( 55 ).…”
Section: Sustained O-glcnacylation Correlates With Increased Phosphormentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al have reported that moderate inhibition of mTOR enhances autophagy while excessive inhibition of mTOR reduces autophagy in trophoblasts. That could be mediated by the functional loop between the O-GlcNAcylation and phosphorylation of Beclin-1 [49]. Additionally, Yang et al have reported AMPK as a negative regulator of autophagy in primary human trophoblasts [50].…”
Section: Upstream Regulators Of Autophagy For Trophoblast Cellsmentioning
confidence: 99%
“…Furthermore, autophagy, a process which is governs the degradation of misfolded proteins and damaged organelles, is important for normal placental developmental activities, such as invasion and vascular remodeling of extravillous trophoblasts (EVT). Studies on HTR8/SVneo cells showed that mTOR signaling also plays a role in regulating autophagy via the modulation of Beclin1 and synaptosome associated protein 29 (SNAP29) O-GlcNAcylation (21). Enhanced autophagy levels have been observed in human and mouse placentas exposed to HIP, as well as trophoblast cells in high-glucose environments (22)(23)(24).…”
Section: Placenta Growth and Developmentmentioning
confidence: 99%